Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) Berbantuan LKS terhadap Hasil Belajar Fisika Siswa SMA Attohiriyah Bodak - Syamsul Hakim; Wahyudi Wahyudi; Ni Nyoman Sri Putu Verawati (Universitas Pendidikan Mandalika, 2018)
[Title: The Effect of Contextual Teaching and Learning (CTL) Model with Student Worksheet Assistance toward Physics Learning Outcomes of Attohiriyah Bodak High School Students]. This research aims to determine the influence of Contextual Teaching and Learning model with student worksheets toward student’s physics study result at SMA Attohiriyah Bodak in academic year 2015/2016. The type of this research was quasi-experiment with nonequivalent control group design. The population in this research were all students in X grade SMA Attohiriyah Bodak with amount student 149 spread out into 6 class. The sample of this research is XB as experiment class and XE as control class were drawn by purposive sampling. The study result obtained was analysis with t-test separated varians, and the results showed tcount = 3.78 and ttable = 2.01 in significant standard 5% and released standard 5. Because Ho rejected and Ha accepted. So, we can conclude that contextual teaching and learning model with student worksheets positive influence toward student’s physics study result at SMA Attohiriyah Bodak academic year 2015/2016